Comparison of laparoscopic and open pancreaticoduodenectomy for the treatment of distal cholangiocarcinoma: A propensity score matching analysis - Zhu, Yuwen; Zu, Guangchen; Wu, Di; Zhang, Yue; Yang, Yang; Wu, Han; Chen, Xuemin; Chen, Weibo (Frontiers in Oncology, 2022)
Background: There are few studies comparing the oncological outcomes of laparoscopic pancreaticoduodenectomy (LPD) and open pancreaticoduodenectomy (OPD) for distal cholangiocarcinoma (DCC). Our objective was to assess the short-term efficacy and long-term survival of LPD and OPD in patients with DCC. Methods: The data of 124 DCC patients who underwent LPD or OPD at the Third Affiliated Hospital of Soochow University from May 2010 to May 2021 were retrospectively analyzed. Propensity score matching was performed to balance the two groups of baseline characteristics. After 1:1 matching, the overall survival (OS) of the two groups was compared by the Kaplan‒Meier method. Univariate and multivariate Cox regression analyses were used to identify independent predictors of OS. Results: The original cohort consisted of 124 patients. Nineteen patients were excluded because of incomplete baseline or follow-up data, and the remaining 105 patients were divided into two cohorts (45 in the LPD group and 60 in the OPD group). The LPD group showed more favorable results in OS analysis (LPD vs. OPD, 56.4 [46.2-66.5] vs. 48.9 [36.4-61.4], months, P=0. 01). PSM analysis identified 30 pairs of patients, and differences between matching groups were still significant (LPD vs. OPD, 67.9[58.2-77.6] vs. 47.4[31.4-67.5], months, P=0.002). Moreover, the LPD group experienced less intraoperative bleeding (LPD vs. OPD, 292.67 vs. 519.17 ml, P=0.002). Univariate analysis showed that surgical modality (P=0.012), carbohydrate antigen 19-9 (P=0.043), carcinoembryonic antigen (P=0.003), neutrophil-to-lymphocyte ratio (P=0.012), blood transfusion (P=0.031), clinically relevant postoperative pancreatic fistula (P<0.001) and lymphatic metastasis (P=0.004) were predictors of OS. Multivariate Cox analysis demonstrated that carbohydrate antigen 19-9 (P=0.048), carcinoembryonic antigen (P=0.031) and lymphatic metastasis (P=0.023) were independent predictive factors of OS. However, adjuvant therapy had no significant effect on the OS of DCC patients after radical pancreaticoduodenectomy (P>0.05). Conclusions: For DCC patients, LPD may be a more recommended procedure because of its advantages over OPD in terms of intraoperative bleeding and long-term survival.